Optimising oscillatory positive expiratory pressure devices for effective airway clearance - Khasawneh, Mohammad (Cranfield University, 2016)
Oscillatory positive expiratory pressure (OPEP) devices are a form of airway clearance techniques that are wildly used in the clinical practice and well accepted by patients. Clinicians and respiratory therapists are responsible for choosing the appropriate OPEP device for their patients. In addition, they are responsible for optimising the mechanical behaviour of the device to achieve effective airway clearance results. The effectiveness of OPEP devices is critically dependent on the properties of the oscillatory pressure wave generated by these devices. However, the pressure wave parameters vary at different settings (flow rates and resistance levels combinations). Despite OPEP devices been around for several years and routinely used in clinical practice, the question remains as to “which settings are appropriate for optimum airway clearance results”. The mechanical behaviour of several OPEP devices has been investigated in previous studies. However, experimental set up variations makes a direct comparison between the results very difficult, especially for devices from different manufacturers. Also, previous attempts to inform the clinical practice on how to use OPEP devices were limited by the lack of technical performance criteria to guide optimising these devices according to patients underlying physiological dysfunction and airway clearance aims. The aim of this research is to characterise the optimum mechanical behaviour of OPEP devices for effective airway clearance. In this research, the mechanical behaviour of OPEP devices was characterised using a validated measurement system and a systematic experiment design that takes into account the findings and limitations of previous studies. The mechanical behaviour was mathematically modelled and validated using regression analysis techniques. Desirability optimisation function was used to characterise OPEP device settings that satisfy optimum technical performance criteria. Based on these findings, the research discussed how OPEP devices could be optimised in clinical practice for different disease groups and airway clearance therapy aims. In the field of airway clearance research, devices evaluation lies at the base of the evidence appraisal hierarchy. In this research, optimum technical performance criteria for effective airway clearance are proposed. This research offers a comprehensive characterisation of the mechanical behaviour of OPEP devices under a unified experimental setup and flow ranges commonly found in clinical practice. Also, this research provided a comprehensive characterisation of the optimum mechanical behaviour of OPEP devices for different disease groups and airway clearance therapy aims. A possible area for future work would be to investigate the pressure wave parameters effect on airway clearance from a fluid dynamic perspective.
Keywords: Airway clearance therapy; airway clearance by oscillation; Acapella; Aerobika; chest physiotherapy; mucus; modelling and optimisation of medical devices